Numerical and experimental investigation of liner top thickness on the formation and penetration performance of explosively formed projectiles - Quan, Pham Hong; Minh, Do Van; Thanh, Tran Dinh (Vietnam Journal of Mechanics, 2025)
This paper presents a detailed investigation, both numerical and experimental, into the influence of liner top thickness (denoted as δ₁) on the formation dynamics and terminal performance of explosively formed projectiles (EFPs). Six structural variants of a 54 mm caliber EFP warhead were modeled using Ansys Autodyn, with top thickness-to-diameter ratios (δ₁/d) ranging from 0.02 to 0.07. The simulations evaluated key performance metrics, including projectile velocity, kinetic energy distribution, penetration depth, and cavity dimensions. Results demonstrated that EFPs with δ₁/d between 0.03 and 0.05 achieved the best overall balance between aerodynamic stability, structural coherence, and penetration effectiveness. Experimental validation for a configuration with δ₁ = 2 mm (δ₁/d ≈ 0.044) showed good agreement in both velocity and cavity geometry. These findings provide robust design guidelines for optimizing EFP liners and confirm the reliability of numerical modeling for preliminary engineering evaluations.